Atelier 4. (Amsterdam : Stedelijk Museum Amsterdam, 1966)
Arons ; Blewanus ; Van den Broek, Jan ; Buys, Hans ; van Golden, Daan ; Gribling, Franck ; Hollenbach, Hans ; Jansen, Jan ; Peters, Ben ; Prinsen, Otto ; Roos, Aart ; Varela, Artur
biog. per kunstenaar
Atelier 4, Stedelijk Museum Amsterdam, 28 oktober - 4 december 1966
Nederlands
boek